Firm size effects in trade credit supply and demand - Lawrenz, Jochen; Oberndorfer, Julia (Journal of Banking & Finance, 2018)
By investigating trade credit usage among SMEs and large companies following the macroeconomic shock of the financial crisis of 2007/08, we identify a firm size effect, which is genuine in the sense that it cannot be entirely explained by financial constraints, external finance dependence or creditworthiness. We find that (i) SMEs, in contrast to large firms, do not display evidence for the inter-firm liquidity redistribution hypothesis. Especially large vulnerable firms did cut down trade credit provision to the detriment of small vulnerable firms. (ii) We document a general substitution effect between bank and trade credit and show that it has strengthened during the crisis among large firms, but not among SMEs. (iii) We provide evidence that the shift in trade credit financing had adverse real effects on investment behaviour of SMEs.